STANDARDISASI SIMPLISIA DAN PENETAPAN KADAR SAPONIN EKSTRAK DAUN Miconia crenata - Deby Sandri Febriyanti Deby (PHARMACIA, 2023)
An invasive plant that has the potential to develop into a medicinal raw material is Miconia crenata. Standardization parameter values are by defining specific and non-specific parameters on simplicia and extracts. The study uses an experimental method, which is an experiment conducted to find out the results of a particular treatment or experiment by studying the standardization of simplicia and extracts as well as the determination of the level of saponins extracted from the Miconia crenata leaf. The macroscopic test results of simplisia leaves Miconia crenata are fine powdered and thick extracts, with a characteristic aromatic scent, a color simplisia brown green and black brown extract with a bitter taste. The microscopic results obtained covered hair, carrier files, oxalate crystals, upper epidermis, sclerenchyma, and lower epiderms with stomata. Phytochemical screening results contain flavonoids, alkaloids, saponins, tannins and steroids. Specific and non-specific parameters on simplicia and Miconia crenata leaf extract have been tested in accordance with MMI and FHI standardization which can potentially be used as standard herbal medicine raw materials. (FHI). For the determination of the saponin levels of Miconia crenata leaf extract using the gravimetric method, the average value of saponins was 17.38%±0.025.